KUPASAN PEMAKAIAN SERBAN KETIKA MENUNGGANG MOTOSIKAL BERDASARKAN FIQH KEUTAMAAN - Ibrahim, Basri (Jurnal Syariah, 2009)
This article aims to analyse if wearing a turban while riding a bike is suitable from the fiqh perspective. Wearing a turban while riding a bike opposes with two forms of Sunnah; Sunnah in Muslim dress code and Sunnah in ensuring life safety. This issue has drawn much attention from numerous parties in our country. This article is based on both library and field research. The library research focused on collecting and analyzing all related information, while field research primarily focused on interviews with the Terengganu State, Director of Road Transport Department. This article proves that wearing turban is inappropriate while riding/operating a bike as it is unable to protect the head area especially the brain from anticipated injuries in the event of an accident. The probability of getting injured in the head is lower when a helmet is worn. Muslims should abide to the current law enforcement set by the authorities in the interest of their own road safety.